Christian Students' Understanding of Love and Its Implementation towards Others at School: Pemahaman Peserta Didik Kristen tentang Kasih dan Implementasinya terhadap Sesama di Sekolah - Christya Hayuning Saputri; Mardiharto; Untari Prihatiningsih (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2022)
In the school environment, especially in schools, students must have problems both internally and externally. These problems need to be solved and appropriate solutions given to overcome them, especially external problems that often occur between friends such as being indifferent, being ostracized by some friends, enmity between friends, which are closely related to the implementation of love for others within the scope of school. The background of this research is that there are Christian students who have not applied love. The purpose of this study was to determine the understanding and implementation of Christian students about love with others at school. By using qualitative methods, it can be concluded that the understanding of Christian students about love and its implementation towards others in schools is, first, that students can understand and understand the understanding of love for others, second, students in the potential of understanding and love, correctly related to Willing to Sacrifice, Generous. Not Judging and forgiving must be based on Bible teaching to be a guide. So that it can have an impact on implementation in schools.